An FPGA-Based Adaptable 200 MHz Bandwidth Channel Sounder for Wireless Communication Channel Characterisation. (1st March 2011) - Ndzi, David L.; Stuart, Kenneth; Toautachone, Somboon; Yang, Yanyan; Dunn, Victor
Abstract : This paper describes the development of a fast adaptable FPGA-based wideband channel sounder with signal bandwidths of up to 200 MHz and channel sampling rates up to 5.4 kHz. The application of FPGA allows the user to vary the number of real-time channel response averages, channel sampling interval, and duration of measurement. The waveform, bandwidth, and frequency resolution of the sounder can be adapted for any channel under investigation. The design approach and technology used has led to a reduction in size and weight by more than 60%. This makes the sounder ideal for mobile time-variant wireless communication channels studies. Averaging allows processing gains of up to 30 dB to be achieved for measurement in weak signal conditions. The technique applied also improves reliability, reduces power consumption, and has shifted sounder design complexity from hardware to software. Test results show that the sounder can detect very small-scale variations in channels.